The role of risk in improving goal setting in performance management practices within public sector: an explorative research in Courts offices in Italy - Capaldo, Guido et al (2018)
The study investigates whether the adoption of a risk-based approach that allows public managers to take into account the context and external not-controllable factors during goal setting may contribute to overcome unintended managerial side effects of performance management (PM) practices that hamper their success within public organizations. An explorative research is carried out on court officials of Italian public administration. The results from this study show that the adoption of a risk-based approach could enhance goal setting within the PM process and provide interesting insights to policy-makers invested of the responsibility to improve the effectiveness of current PM procedures. Reproduced.
Keywords: Government enterprises - Service rating